EFFECT OF SOYBEAN (GLYCINE MAX L. MERR) INTERCROPPING INTO RHODESGRASS (CHLORIS GAYANA KUNTH.) ON DRY MATTER YIELD, CRUDE PROTEIN, AND SILAGE CHARACTERISTICS GROWN IN SOUTHWEST JAPAN - Y. S. Prasojo; M. Niimi; M. M. Rahman; G. Ishigaki; R. Akashi (Journal of Animal and Plant Sciences, 2022)
This study aimed to investigate the quantify yield and silage quality response of forage soybean (Glycine max L. Merr) intercropping into rhodesgrass (Chloris gayana Kunth.) cultivation compare to monoculture rhodesgrass in warm temperate zone. Rhodesgrass and soybean were intercropped in 2017 and 2018 at Sumiyoshi Livestock Science Station, University of Miyazaki in southwest Japan. As the results, there were no differences between the height of monocultured rhodesgrass (MC) and intercropped rhodesgrass (IC). Height of soybean was less than rhodesgrass. Dry matter yield (DMY) was not significantly different between MC and IC in both years. For soybean ratio of intercropped total yield, the two-years-average was 18.3%. The lower soybean ratio of intercropped total yield in 2018 (13.3%) than those in 2017 (30.8%) seems to be caused by the larger rhodesgrass DMY. Crude protein (CP) content of IC (11.0%) was not significantly higher than that of MC (10.6%). There was no significant difference of CP yield between MC (28.3 kg/10 a) and IC (22.3 kg/10 a). All silages produced in this two-year experiment had only trace amounts of organic acids and volatile basic nitrogen regardless of the presence of soybean. In conclusion, the existence of soybean did not affect the silage quality. Early growth type soybean cultivar, appreciate harvesting time and fertilizer improvement might be increase DMY and CP with soybean intercropping.
Keywords: intercropping system; rhodesgrass; silage characteristic; soybean